Fracture processes numerical modeling of elastic-brittle bodies with statistically distributed subregions strength values (Fracture and Structural Integrity, 2024)
This work is devoted to the fracture processes numerical modeling of elastic-brittle bodies taking into account the statistical distribution of subregions strength values and stress concentration. The novel formulation of the boundary value problem and its solution algorithm are developed. The loading diagrams obtained in computational simulations, the corresponding growth curves of the destroyed elements relative number and the damaging process kinetics are analyzed. The presence of the postcritical deformation stage at the macro-level is noted. The influence of the strength properties distribution range and the depth of the concentrator on the maximum load value and the damage evolution is determined. The significant influence of the finite elements’ properties distribution on the fracture processes modeling results is concluded.
Keywords: Fracture; Finite element method (FEM); Numerical modeling; Brittle body; Strength properties distribution